5x-3+4x-24=3x+2+4x-9

Simple and best practice solution for 5x-3+4x-24=3x+2+4x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3+4x-24=3x+2+4x-9 equation:


Simplifying
5x + -3 + 4x + -24 = 3x + 2 + 4x + -9

Reorder the terms:
-3 + -24 + 5x + 4x = 3x + 2 + 4x + -9

Combine like terms: -3 + -24 = -27
-27 + 5x + 4x = 3x + 2 + 4x + -9

Combine like terms: 5x + 4x = 9x
-27 + 9x = 3x + 2 + 4x + -9

Reorder the terms:
-27 + 9x = 2 + -9 + 3x + 4x

Combine like terms: 2 + -9 = -7
-27 + 9x = -7 + 3x + 4x

Combine like terms: 3x + 4x = 7x
-27 + 9x = -7 + 7x

Solving
-27 + 9x = -7 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-27 + 9x + -7x = -7 + 7x + -7x

Combine like terms: 9x + -7x = 2x
-27 + 2x = -7 + 7x + -7x

Combine like terms: 7x + -7x = 0
-27 + 2x = -7 + 0
-27 + 2x = -7

Add '27' to each side of the equation.
-27 + 27 + 2x = -7 + 27

Combine like terms: -27 + 27 = 0
0 + 2x = -7 + 27
2x = -7 + 27

Combine like terms: -7 + 27 = 20
2x = 20

Divide each side by '2'.
x = 10

Simplifying
x = 10

See similar equations:

| -2(6+4b)=-6b | | 10y-4g-8=20 | | r/10+1.1=0.3 | | 2n+3.5=6.7 | | W^2+7=w^3+9 | | (A^-3b6-4/a^7b^3)(a^3b^4/a^-3b^-3)^2 | | 5x-3(x-5)=15 | | 2p-2=14+6p | | 6(r+7)=35+5r | | 3x=56+7(9)y | | 4t+8t=60 | | 9m+108=9m*5 | | 3k-5=2(k+1) | | 1/2(8x-5/11)-10/11(5x+3/8)=1/4(2x+5) | | X/3-8=-15 | | d/-4+3f=14 | | 5t+8t=60 | | 12=-4-11 | | -66=4+10x | | 3x+12=2x+8 | | m+12=5 | | 3z-16-z+6=0 | | 4/5+15m=v/w | | 2(1)-2=9 | | 2x+4(x-13)=2 | | -4(7+4m)-3=-8m+9 | | 7x-2=4x+4+3x-6 | | 448=3x^2+2x-8 | | (3)(5)(7)=n | | j-(-1.6)=-3.7 | | 1.15x=180000 | | t-3=25 |

Equations solver categories